Pengaruh Pelatihan Pembuatan Makanan Pendamping (MP-ASI) Berbahan Herbal pada Ibu Batita terhadap Pengetahuan dan Keterampilan Pembuatan Makanan Pendamping (MP-ASI) - Komala Dewi Muslimin; Yuliana Yuliana; Tressan Eka Putri S. Katili; Nurlismi Subbe; Ismi Choirunnisa (Pusat riset dan Inovasi Nasional, 2026)
The provision of herbal-based complementary feeding (MP-ASI) has several positive impacts, including improving mothers’ understanding and skills in preparing complementary foods from local food ingredients in accordance with local customs and socio-cultural practices, thereby enabling mothers to independently continue providing local complementary feeding. This study aimed to determine the effect of training on the preparation of herbal-based complementary feeding for mothers of children under three years old on their knowledge and skills in preparing complementary feeding. This study employed a quasi-experimental research design and was conducted at Kanda Public Health Center. The population consisted of all mothers with children under three years old in the working area of Kanda Public Health Center, totaling 245 mothers. The sample size in this study was 35 respondents. The results of the analysis showed that there was a significant difference in mothers’ knowledge before and after the training on complementary feeding preparation, with a significance value of 0.000.